2017
DOI: 10.1097/dbp.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Family Socioeconomic Status Moderates Associations Between Television Viewing and School Readiness Skills

Abstract: Television viewing is negatively associated with children's school readiness skills, and this association increased as family income decreased. Active efforts to reinforce AAP guidelines to limit the amount of television children watch should be made, especially for children from middle- to lower-income families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 33 publications
4
39
2
1
Order By: Relevance
“…The results showed that the association between children’s screen time and cognitive development was unclear, waiting for more evidence to figure it out. Children with excessive screen time were associated with an increased risk of delayed language development [ 28 , 66 , 67 , 69 , 71 , 72 ], language learning problems [ 23 , 60 , 73 ], mathematics learning problems [ 23 , 68 , 69 ], and reading problems [ 68 , 70 ]. A total of four studies reported a negative association between screen time and motor developments, and children being exposed to excessive screen time were more likely to suffer from fine motor [ 73 ] development problems and gross motor [ 23 , 73 ] development problems.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the association between children’s screen time and cognitive development was unclear, waiting for more evidence to figure it out. Children with excessive screen time were associated with an increased risk of delayed language development [ 28 , 66 , 67 , 69 , 71 , 72 ], language learning problems [ 23 , 60 , 73 ], mathematics learning problems [ 23 , 68 , 69 ], and reading problems [ 68 , 70 ]. A total of four studies reported a negative association between screen time and motor developments, and children being exposed to excessive screen time were more likely to suffer from fine motor [ 73 ] development problems and gross motor [ 23 , 73 ] development problems.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently with existing literature in the field, school readiness scores were strongly positively associated with better executive function scores in the cognitive assessment and strongly negatively associated with the parent-completed inventory. The three aspects of executive function (working memory, inhibition/attention and cognitive flexibility) assessed during the study are considered fundamental for school readiness [ 44 ]. Greater ability in cognitive flexibility, attention, inhibition and working memory is crucial in self-regulation and subsequently in allowing children to organise their thinking, minimise reactivity, increase social competence and ultimately support early learning, school readiness and school achievement [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to electronic screen‐based media might be particularly detrimental to the development of EF; however, evidence to date is mixed and differences in results might depend upon context or platform of viewing, media content, or child age. In groups of older children, increased time spent watching television is negatively associated with EF, perhaps due to its impact on attentional capacities (Nathanson, Alade, Sharp, Rasmussen, & Christy, ; Ribner, Fitzpatrick, & Blair, ). This has been shown experimentally: Lillard and Peterson () found that 4‐year‐old children who watched a fast‐paced cartoon, rather than either an educational cartoon or no television, performed significantly worse on EF tasks immediately after watching.…”
Section: Introductionmentioning
confidence: 99%